Novel Al based nanoquasicrystalline alloys. (January 2022) - Galano, M.; Audebert, F.
Abstract: The Al-based nanoquasicrystalline alloys are modern light weight alloys that respond to a strategy to develop new Al-based alloys with excellent combination of properties over a large range of temperatures when compared with standard aluminium alloys. The review describes their historical development, the manufacturing processes used for the alloy production and the microstructure obtained. A summary of the different systems and alloying elements used in the development is presented and their stability is discussed. Several properties have been studied with particular focus on mechanical and structural applications, which are discussed together with their potential applications.